2016
DOI: 10.1155/2016/8351427
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Concentration and Other Salivary Changes after Insertion of New Complete Dentures in Edentulous Subjects

Abstract: Objective. To assess changes in levels of salivary nitric oxide (NO) after insertion of new complete dentures and its association with clinical and salivary parameters. Methods. Nineteen fully edentulous subjects were included, mean age 64.4. Unstimulated whole saliva was collected before and after insertion of the dentures, at follow-up visits, and after 12 months. The concentration of the final stable NO product (nitrite) was measured by a colorimetric assay based on the Griess reaction. Clinical parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…In addition to that, another study reported a statistical significance of pH values before and after the CDs insertion [22]. Others, however, have not found significant changes in pH values [4,23]. Findings of our study are in correlation with previous findings that pH is significantly different before and after dentures insertion [24].…”
Section: Disscusionsupporting
confidence: 88%
See 2 more Smart Citations
“…In addition to that, another study reported a statistical significance of pH values before and after the CDs insertion [22]. Others, however, have not found significant changes in pH values [4,23]. Findings of our study are in correlation with previous findings that pH is significantly different before and after dentures insertion [24].…”
Section: Disscusionsupporting
confidence: 88%
“…Stress may relate to usual transitory problems that arise after the insertion of new CDs, such as discomfort, functional difficulties, sore spots, injured mucosa and different levels of pain, thus extending the period of adaptation [4]. Introducing new CDs may also be a predisposing factor for the onset of salivary changes that affect oral homeostasis and oral mucosal health [4].…”
Section: сажетакmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels of patient adaptation to the dentures and the presence of injuries in the mucosa were assessed and rated on a three‐point ordinal scale during the post‐insertion appointments . The level of patient adaptation to the dentures was rated as (a) report of favourable adaptation and continuous use of the dentures—absence of or minimal complaints; (b) report of difficult adaptation or intermittent use of the dentures—moderate to severe complaints; or (c) report of extreme difficulties and sporadic or no use of the dentures—severe complaints.…”
Section: Methodsmentioning
confidence: 99%
“…The levels of patient adaptation to the dentures and the presence of injuries in the mucosa were assessed and rated on a three-point ordinal scale during the post-insertion appointments. 20 The level of patient adaptation to the dentures was rated as (a) report of favourable adaptation and continuous use of the dentures-absence of or minimal complaints; (b) report of difficult adaptation or intermittent use of the dentures-moderate to severe complaints; or (c) report of extreme difficulties and sporadic or no use of the dentures-severe complaints. Injuries to the supporting mucosa were assessed and rated as follows: (a) absent; (b) one or two sore spots or ulceration evidenced by visual inspection, digital pressure or tissue compression with the denture; or (c) multiple sore spots or ulcerations evidenced by visual inspection, digital pressure or tissue compression with the denture.…”
Section: Clinical Outcomesmentioning
confidence: 99%